2006
DOI: 10.1007/s10722-004-6095-z
|View full text |Cite
|
Sign up to set email alerts
|

Species Diversity in Wheat Landrace Populations from two Regions of Ethiopia

Abstract: Wheat (Triticum spp.) landrace populations in Ethiopia are mostly species mixtures. However, no quantitative data is available with regard to their species components. We studied here 32 wheat landrace populations originating from two regions (Bale and Wello). A total of 2559 individual plants, 45-110 plants representing each population, were classified into their species components. Five tetraploid (2n ¼ 4x ¼ 28) and one hexaploid (2n ¼ 6x ¼ 42) wheat species were found in mixtures of varying proportions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Tesemma et al (1993) stated that Ethiopian wheat landraces are usually mixtures of different agro-types having wider gene pools within one population that can buffer the change of climatic and edaphic factors. Eticha et al (2006) also reported mixtures of five tetraploid wheat landraces and hexaploid wheat in varying proportions in one population of germplams collected from Bale and Welo regions. The species mixtures/agro-types might have an advantage for the farmers when grown in the same field: to add variety to the diet and, on the other hand, to carry diverse genes for disease and pest resistances and adaptability to changing climatic factors (Bekele, 1984).…”
Section: Discussionmentioning
confidence: 91%
“…Tesemma et al (1993) stated that Ethiopian wheat landraces are usually mixtures of different agro-types having wider gene pools within one population that can buffer the change of climatic and edaphic factors. Eticha et al (2006) also reported mixtures of five tetraploid wheat landraces and hexaploid wheat in varying proportions in one population of germplams collected from Bale and Welo regions. The species mixtures/agro-types might have an advantage for the farmers when grown in the same field: to add variety to the diet and, on the other hand, to carry diverse genes for disease and pest resistances and adaptability to changing climatic factors (Bekele, 1984).…”
Section: Discussionmentioning
confidence: 91%
“…The evaluated lines of Polish wheat were characterized by high RSD values of most shape and color descriptors. High intraspecies variation can be attributed to the low commercial interest in this species; therefore, conscious efforts to narrow down the gene pool of Polish wheat were not made throughout the centuries [53]. A comparison of the variations in the lines of the analyzed wheat species suggests that rarely farmed ancient species are characterized by a larger gene pool and consequently, greater variations in phenotypic traits [54].…”
Section: Discussionmentioning
confidence: 99%
“…Emmer wheat is cultivated in marginal lands in almost all regions of the country (Gonder, Gojam, Welo, Tigray, Shewa, Bale, Arsi, Hararge, Sidamo and Gamu Gofa), in altitudinal ranges of 1,800-3,000 m (Institute of Biodiversity Conservation of Ethiopia, unpublished). It is one of the major cereal crops in the Bale zone of south eastern Ethiopia (Demissie and Hailegiorgis 1985) and is consciously grown in mixtures with other tetraploid wheats and bread wheat by farmers from Bale and Welo (Eticha et al 2006). This practice allows gene flows between wheat species, reduces the risk of breakdown due to diseases or other stresses, and increases the nutritional value of the production (Bekele 1984; Worede 1997).…”
Section: Present Cultivationmentioning
confidence: 99%